Synthesis and molecular docking of 1, 2, 3-triazole-based sulfonamides as aromatase inhibitors. Issue 13 (1st July 2015) - Pingaew, Ratchanok; Prachayasittikul, Veda; Mandi, Prasit; Nantasenamat, Chanin; Prachayasittikul, Supaluk; Ruchirawat, Somsak; Prachayasittikul, Virapong
Graphical abstract: Compound34 : IC50 0.2 μM, SI >435. Abstract: A series of 1, 4-disubstituted-1, 2, 3-triazoles (13 –35 ) containing sulfonamide moiety were synthesized and evaluated for their aromatase inhibitory effects. Most triazoles with open-chain sulfonamide showed significant aromatase inhibitory activity (IC50  = 1.3–9.4 μM). Interestingly, the meta analog of triazole-benzene-sulfonamide (34 ) bearing 6, 7-dimethoxy substituents on the isoquinoline ring displayed the most potent aromatase inhibitory activity (IC50  = 0.2 μM) without affecting normal cell. Molecular docking of these triazoles against aromatase revealed that the compounds could snugly occupy the active site of the enzyme through hydrophobic, π–π stacking, and hydrogen bonding interactions. The potent compound34 was able to form hydrogen bonds with Met374 and Ser478 which were suggested to be the essential residues for the promising inhibition. The study provides compound34 as a potential lead molecule of anti-aromatase agent for further development.